Visual and ocular findings in a family with X-linked cone dysfunction and protanopia. (3rd September 2021) - Holmquist, Dag; Epstein, David; Olsson, Monica; Wissinger, Bernd; Kohl, Susanne; Hengstler, Jürg; Tear-Fahnehjelm, Kristina
ABSTRACT: Background : Bornholm eye disease (BED) is a rare X-linked cone dysfunction disorder with high myopia, amblyopia, and color vision defects. Materials and methods: Visual and ocular outcomes in a family where two of five siblings had molecularly confirmed BED are reported. Ophthalmological assessments included best-corrected visual acuity (BCVA), color vision test, and optical coherence tomography (OCT). Medical records, electroretinography (ERG), and genetic analyses were re-evaluated. Results: Two male siblings had confirmed BED with myopia and protanopia. The younger brother had high myopia, subnormal BCVA, and ocular fundi that showed tilted discs, crescent shaped peripapillary atrophy, and visible choroidal vessels. OCT confirmed retinal and choroidal atrophy. The older brother was lightly myopic with normal/subnormal BCVA and subtle findings in the fundi. Both brothers had abnormal ERG recordings with a decreased cone response. They also had a structurally intact OPN1LW/OPN1MW gene cluster. The OPN1LW gene was shown to carry a deleterious variant combination in exon 3 known to result in mis-splicing of opsin mRNA and acknowledged as LIAVA amino acid delineation (Leu153-Ile171-Ala174-Val178-Ala180), while the OPN1MW gene exon 3 showed a non-pathogenic variant combination (MVVVA). Another normal-sighted brother carried another wildtype variant combination (LVAIS) in exon 3 of the OPN1LW gene. Conclusions: The two affected brothers demonstrated a large variability in their phenotypes even though the genotypes were identical. They presented a disease-associated haplotype in exon 3 of OPN1LW that has been described as the molecular cause of BED.